Mycophagous gall midges (Diptera, Cecidomyiidae: Lestremiinae, Micromyinae, Winnertziinae, Porricondylinae): first records in Sweden and descriptions of closely related new species from elsewhere - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2017)
Thirty species of gall midges, Cecidomyiidae, of the mycophagous subfamilies Lestremiinae, Micromyinae, Winnertziinae, and Porricondylinae are reported from Sweden for the first time, including several extremely seldom collected species. Genera newly found in Sweden are Allaretella Meyer & Spungis (in Lestremiinae), Tekomyia Möhn (in Micromyinae), Nikandria Mamaev (in Winnertziinae), Arctepidosis Mamaev, Dallaiella Mamaev, Epicola Spungis, and Lamellepidosis Mamaev (all in Porricondylinae). Peromyia trimera (Edwards, 1938) stat. rev. is revived from the synonymy with P. ramosa (Edwards, 1938). Descriptions of the male morphology are provided of the micromyines Aprionus aberrantis Mamaev, Campylomyza abjecta Mamaev, Peromyia leveillei Kieffer (type species of the genus Peromyia Kieffer), Peromyia trimera, and Tekomyia populi Möhn; the winnertziine Nikandria brevitarsis Mamaev; and the porricondylines Arctepidosis jamalensis Mamaev, Dallaiella petrosa Mamaev, and Lamellepidosis spungisi Mamaev. Bryomyia amurensis Mamaev & Økland, Campylomyza abjecta Mamaev, and Peromyia gotohi Jaschhof (all in Micromyinae) are new records in the Western Palearctic. New species described are Peromyia sororia spec. nov. from Japan, a close relative of P. leveillei, and Nikandria australis spec. nov. from New Zealand, only the second species in the genus Nikandria Mamaev. An intersexual specimen of Lamellepidosis spungisi with female antennae and male genitalia is described.